GALODO - Hengky Septiawan; Wimbrayardi Wimbrayardi; Marzam Marzam (SENDRATASIK UNP, 2012)
This swan song of inspiration pursuant to ( 1) at galodo disaster that happened in West Sumatera. Target of this masterpiece is (2) for the depicting of musical instrument and atmosphere that happened at the time of galodo disaster come knock overing a area, later;then how situation of society which born down upon the the disaster before and after that disaster knock over. Form which [in] presenting in this swan song in the form of (3) and vocal game of modern and traditional castanets which in presenting in such a manner so that can depict atmosphere which wish in reaching.